Enhancing mechanical and surface properties of eucalyptus wood - Pertuzzatti, Anderson; Tondi, Gianluca; Coldebella, Rodrigo; W. Dalla Costa, Henrique; A. Gatto, Darci; L. Missio, André (Maderas. Ciencia y Tecnología, 2020)
Eucalyptus is one of the most fast-growing trees. Therefore, in the last decades it has been extensively planted and harvested so that nowadays Eucalyptus is one of the most popular trees of the planet. There are many genres of this plant and they are often treated as a large bunch of the same timber characterized by moderate mechanical and surface properties which hinder their usage for any sight application (e.g. flooring, cladding, ceiling). In this study four species of Eucalyptus: E. grandis, E. dunnii, E. cloeziana and E. tereticornis were undergone to densification through hydro-thermo-mechanical treatment (HTM) first and then to oil heat-treatment (OHT) in order to improve their mechanical properties and hydrophobicity. It was observed that low density species (E. grandis) reaches higher compression degrees while heavier species (E. tereticornis) reach densities over 800 kg/m³; however, HTM decrease the variability of the properties. Treatments at higher temperature (160 °C) involves higher compression degree, lower set-recovery and higher surface hydrophobization, but also weaker mechanical properties. The hot oil post- treatment helps to contain the springback effect and to reduce the wettability of each specimen. Densified samples present similar surface hardness. The tailored application of the two treatments improves the properties of every Eucalyptus which can gain market also for nobler end-usages.